Answer
a) Check graph. As t increases, x and y get smaller.
b) $y=(\frac{3}{4})x-(\frac{1}{4})$
![](https://gradesaver.s3.amazonaws.com/uploads/solution/929c9837-9a72-456e-89c2-6b176851762d/result_image/1513126528.png?X-Amz-Algorithm=AWS4-HMAC-SHA256&X-Amz-Credential=AKIAJVAXHCSURVZEX5QQ%2F20250215%2Fus-east-1%2Fs3%2Faws4_request&X-Amz-Date=20250215T142643Z&X-Amz-Expires=900&X-Amz-SignedHeaders=host&X-Amz-Signature=e84b005187e7485399ef4290c9fd0d6e4f4d5df8fcb86a3e5e0a875d0d17294c)
Work Step by Step
a) x = 3 - 4t
y = 2 - 3t
When,
t= -3 x=15 y=11
t= -2 x=11 y=8
t= -1 x=7 y=5
t= 0 x=3 y=2
t= 1 x=-1 y=-1
t= 2 x=-5 y=-4
t= 3 x=-9 y=-7
b)
$x=3-4t$
$x-3=-4t$
$(x-3)\div(-4)=t$
$y=2-3t$
$y=2-3((x-3)\div(-4))$
$y=2-((3x-9)\div(-4))$
$y=2+((3x-9)\div(4))$
$y=(8\div4)+(3x-9)\div(4)$
$y=(8+3x-9)\div(4)$
$y=(3x-1)\div(4)$
$y=(3x\div(4))-(1\div(4))$
$y=(\frac{3}{4})x-(\frac{1}{4})$